ANALISA FILM ANIMASI FROZEN DENGAN PENDEKATAN SEMIOTIKA - Jurnal Nurul Azmi; Indra Irawan (Educraf : Journal Of Craft Education, Craft Design And Creative Industries, 2022)
Disney lifted the fairy tale entitled The Snow Queen by Hans Christian Andersen into a film called Frozen in 2013. In the Frozen film, Disney keeps several moral messages in the film. After observing the film, the focus of the message is the message of brotherhood, namely sibling rivalry in this case is the relationship between siblings. Disney conveys the message through the main characters Anna and Elsa. Therefore, this study was conducted to find out how the characters in the Frozen film narrative can describe this sibling rivalry that is told in the Frozen film. The research uses the semiotics of Saussure and the semiotics of Charles Sanders Pierce. So it is known that the characters and their narratives affect each other how the message is delivered in the film. Narrative and characters are one unit that builds the story. The characters of Anna and Elsa appear as representations of siblings in human life where as a form of human relations with other humans in the social sphere, it is not uncommon for siblings to experience this sibling rivalry.